Space Net Capture Parameters Analysis Considering Impact Dynamics - Ming Zhen; Lu Cao; Le-Ping Yang; Tao Sheng; Hai-Tao Liu (Space: Science & Technology)
Rapidly increasing space debris poses a serious threat to space activities. Space nets are promising in removing space debris. The impact response of space nets and space debris is rarely investigated despite its importance for a successful net capture. In the present paper, a new rhombic-mesh net-based impact dynamic model is established with the appending constraint method. A ground net impact test is conducted to validate the developed model, after which the dynamic characteristics of space net are explored based on numerical simulations. Then, space net capture parameters are firstly analyzed considering impact dynamics. It is found that the impact force during the impact process contributes to net wrapping and net closing, and the tether in the impact area is likely to reach a maximum force value. Moreover, the energy of a space net is transferred drastically, which can well mitigate the impact response during the impact process. As the impact kinetic energy of the space net increases, the observed impact response becomes drastic. Furthermore, the influence of the impact position is examined, showing that an eccentric impact is negatively correlated with net wrapping and closing.